Vaccination investigation : the history and science of vaccines - Haelle, Tara (Twenty-First Century Books, 2018)
Documents the history and science behind vaccines, and discusses the controversies surrounding their use, and the events that prompted those arguments. Provides diagrams, charts, graphs, personal stories, and interesting statistics to simply discuss all elements of vaccinations in a balanced way.